172k views
2 votes
How to solve 8(4-r)=-6(3+r)​

User Chriscosma
by
5.7k points

1 Answer

5 votes

Answer:


\boxed{\bold{r=25}}

Step By Step Explanation:

Expand
\bold{8\left(4-r\right): \ 32-8r}

Expand
\bold{-6\left(3+r\right): \ -18-6r}

Rewrite Equation


\bold{32-8r=-18-6r}

Subtract 32 From Both Sides


\bold{32-8r-32=-18-6r-32}

Simplify


\bold{-8r=-6r-50}

Add 6r To Both Sides


\bold{-8r+6r=-6r-50+6r}

Simplify


\bold{-2r=-50}

Divide Both Sides By -2


\bold{(-2r)/(-2)=(-50)/(-2)}

Simplify


\bold{r=25}

User Nathan Wiles
by
5.5k points